The Effect of Applying Quality Standards on the Institutional Performance in the Public Sector in the Sultanate of Oman: Case Study of the Alraffd Fund - Alharthy, Fahad; Hamouri, Mohammed (The Arab Journal of Administration, 2022)
The thesis aims to evaluate the effectiveness of applying the quality standards in the institutional performance in the public sector in the Sultanate of Oman by considering (case study in AlRaffd fund). The thesis discussed the problem of the form of quality standard implementation, and the problem was in that organizations where the quality standards was just randomly implemented without measuring the standards effectiveness in performance. The target population of this study are employee in different levels in AlRaffd fund which are currently ( 200 ) staff members., the linear regression method, the Cronbach alpha constant) and was used (FaceValidity) to verify the reliability of the empirical data analysis. This study investigation has come up with the following findings: There are clear enhancement in staff performance and clarity of the funding process Moreover, the support of top management and the involvement of employees in adopting the quality standards have a positive impact in the application process and reducing change resistance. Based on the previous results, the study suggests several recommendations such as: The administration should work on designing a model to measure the maturity level of applying the standard’s issuing annually a special classification that is a measure of the extent of development for all departments, in additional The training of employees to apply quality programs and standard’s should be continuously and an essential part of the annual training plans of the fund.